2017
DOI: 10.1128/jcm.00616-17
|View full text |Cite
|
Sign up to set email alerts
|

Use of Nucleic Acid Amplification Testing for Diagnosis of Extragenital Sexually Transmitted Infections

Abstract: Nucleic acid amplification testing (NAAT) is the preferred method to detect Chlamydia trachomatis and Neisseria gonorrhoeae, but no commercial tests are cleared by the U.S. Food and Drug Administration for use with extragenital swab samples. This study evaluated the performance of the Gen-Probe Aptima Combo2 assay (Aptima) and the Cepheid Xpert CT/NG assay (Xpert) to detect C. trachomatis and N. gonorrhoeae in rectal and pharyngeal samples from 224 men and 175 women reporting a history of anal receptive sexual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 22 publications
0
10
0
2
Order By: Relevance
“…Our search yielded a total of eight publications, 4,20-24,28,29 five [20][21][22][23][24] of which met our inclusion criteria. We excluded three studies because they were not evaluation studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our search yielded a total of eight publications, 4,20-24,28,29 five [20][21][22][23][24] of which met our inclusion criteria. We excluded three studies because they were not evaluation studies.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies evaluating extragenital testing performance for CT and NG detection by the Xpert CT/NG show high per cent agreement with comparison assays; however, because of the limited sample sizes of CT-and NG-positive cases, the precision around the positive per cent agreement is low. [20][21][22][23][24] Therefore, we aimed to combine data from all published studies of the performance of extragenital testing with Xpert CT/NG to better assess positive per cent agreement.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the result of NG analysis in sample type showed that I 2 values were lower than 50%, indicating low heterogeneity. In terms of gender, I 2 values of specificity in “female” were slightly higher than 50%, while I 2 values of “male” were lower than 50%, indicating low heterogeneity in “female,” but not in “male.” After in-depth study of these fourteen studies, it was believed that the reasons for the heterogeneity might be the following: (1) the specimens collected were either degraded or poorly mixed in the study [ 24 ], (2) the improper behavior of the patients when collecting the sample resulted in the incomplete specimens [ 28 ], and (3) before collecting vaginal specimens, female patients underwent vaginal cleansing [ 25 ]. The sensitivity and specificity of CT and NG in sample type were both greater than 0.9, and the specificity of NG was 1.…”
Section: Discussionmentioning
confidence: 99%
“…Routine screening for pathogens associated with STIs on an annual basis is recommended for all pregnant women, all sexually active females <25 years of age, and at-risk MSM. 5,31 To date, nucleic acid amplification tests (NAATs) are accepted worldwide as an important method for screening causative agents of STIs with several approved commercial molecular panels available. [32][33][34][35] In addition, several emerging nucleic acid amplification platforms combined with fully and partially automated instrumentation are available for targeting multiple microorganisms in a single test reaction.…”
Section: Discussionmentioning
confidence: 99%